Crew and Aircraft Electronic Market - Luis Brochado Pinto Reis (2017)
In the Air Transportation domain, a disruption in an operational plan means a flight that for some reason (due to an irregular event) can't meet the planned schedule, causing delays or cancelled flights. Disruptions can be one of two types, a massive one, which makes impossible to fly in the affected area safely and leads to cancelled flights, or a smaller and most frequent one, which cause delays. Airline companies lose between 2% to 3% of their annual revenue, as consequence of these disruptions. The impact caused by smaller disruptions in companies' profits can be reduced at least by 20%, through a better Recovery Process. Resulting from the lack of collaboration between airline companies, operations recovery works in a restricted solution space, so, to wider this space, this dissertation proposes the usage of a Multi-Agent System based Electronic Market. Airline companies will use the electronic market to negotiate their needs in order to apply their optimal recovery plan. In the specific case of this dissertation, the Airline Operations Control Center (AOCC), which is the entity responsible for dealing with irregular operations, will be considered the buyer agent and the other airline companies the seller agents. The negotiation object is an abstraction named Flight, which includes aircraft and crew members, based on what is needed to minimize the disrupted flight delay. The main characteristics to identify a flight are its cost and availability, this means that if a flight has the same cost and availability that another, it is considered the same even if the resources asked in the market are distinct. The market works on AOCC's feedback over the proposals committed on each round, by the sellers interested in leasing the asked resource(s), leading to new proposals (renegotiating the same flight or another one) until all sellers refuse to negotiate any further. Then, buyer agent informs the seller who proposed the most advantageous solution that his proposal has been accepted and informs all the others that their proposals have been rejected. The main goal of the AOCC is to minimize the costs caused by any disruption, what we consider can be better achieved by leasing resources from other companies. In order to validate this concept and to understand whether it is advantageous or not, it will be necessary to evaluate if the results obtained with recourse to the electronic market are more cost-effective than the solutions obtained with each company's own resources.